Mānavadharmaśāstraīkā Bhaagovindarājīyā : bhāgadvayātmakasyaīkāakopetasyamānavadharmaśāstrasyapur aarupeakalpitā - Govindarāja, 16th cent (Gaapatakrsājīnāmakamudrāyantralaya, 1886)
Supercommentary with six other commentaries on Mānavadharmaśāstra of Manu, ancient text on Hindu law.